The business trip [large type] - Garcia, Jessie, 1970- (Thorndike Press large print thriller, adventure, and suspense, 2025)
"Stephanie and Jasmine have nothing and everything in common. The two women don't know each other but are on the same plane. Stephanie is on a business trip and Jasmine is fleeing an abusive relationship. After a few days, they text their friends the same exact messages about the same man--the messages becoming stranger and more erratic. And then the two women vanish. The texts go silent, the red flags go up, and the panic sets in. When Stephanie and Jasmine are each declared missing and in danger, it begs the questions: Who is Trent McCarthy? What did he do to these women--or what did they do to him?"--